Enzymatically triggered peptide hydrogels for 3D cell encapsulation and culture‡. (12th June 2014) - Szkolar, Laura; Guilbaud, Jean‐Baptiste; Miller, Aline F.; Gough, Julie E.; Saiani, Alberto; Morelli, Giancarlo; Toniolo, Claudio; Venanzi, Mariano
<x xml:space="preserve">Abstract</x> We have investigated the possibility of using enzymatically triggered peptide hydrogels for the encapsulation and culture of cells. Based on recent work done on the enzymatically triggered gelation of FEFK (F, phenylalanine; E, glutamic acid; K, lysine) using thermolysin, a protease enzyme from Bacillus Thermoproteolyticus Rokko, we have investigated the possibility of using this gelation triggering mechanism to encapsulate cells within a 3D hydrogel matrix. First, the properties of enzymatically triggered hydrogels prepared in phosphate buffer solution were investigated and compared with the properties of hydrogels prepared in HPLC grade water from our previous work. We showed that the use of phosphate buffer solution allowed the production of hydrogels with very high shear moduli (>1 MPa). The gelation kinetics was also investigated, and the mechanical properties of the system were shown to closely follow the synthesis of the octapeptide by the enzyme through reverse hydrolysis. In a second phase, we developed, on the basis of information acquired, a facile protocol for the encapsulation of cells and plating of the hydrogel. Human dermal fibroblasts were then used to exemplify the use of these materials. FEFEFKFK octapeptide hydrogels prepared under the same conditions and with the same mechanical properties were used as a control. We showed that no significant differences were observed between the two systems and that after a decrease in cell number on day 1, cells start to proliferate. After 5 days of culture, the cells can be seen to start to adopt a stretched morphology typical of fibroblasts. The results clearly show that the protocol developed minimises the potential detrimental effect that thermolysin can have on the cells and that these enzymatically triggered hydrogels can be used for the 3D encapsulation and culture of cells. Copyright © 2014 European Peptide Society and John Wiley & Sons, Ltd.